2015
DOI: 10.1128/jvi.03253-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus M2 Protein Ion Channel Activity Helps To Maintain Pandemic 2009 H1N1 Virus Hemagglutinin Fusion Competence during Transport to the Cell Surface

Abstract: The influenza virus hemagglutinin (HA) envelope protein mediates virus entry by first binding to cell surface receptors and then fusing viral and endosomal membranes during endocytosis. Cleavage of the HA precursor (HA0) into a surface receptor-binding subunit (HA1) and a fusion-inducing transmembrane subunit (HA2) by host cell enzymes primes HA for fusion competence by repositioning the fusion peptide to the newly created N terminus of HA2. We previously reported that the influenza virus M2 protein enhances p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 70 publications
(103 reference statements)
2
42
0
Order By: Relevance
“…Protease sensitivity and Western blotting. The whole viral particles and purified HA proteins have successfully been used to demonstrate the acidic pH-induced HA conformational changes and HA sensitivity to proteolysis (15,38,(42)(43)(44)(45)(46). Following the acidic pH-induced conformational change of HA, L-(tosylamido-2-phenyl ethyl) chloromethyl ketone (TPCK)-treated trypsin digests the HA1 subunit but not the HA2 subunit (42).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protease sensitivity and Western blotting. The whole viral particles and purified HA proteins have successfully been used to demonstrate the acidic pH-induced HA conformational changes and HA sensitivity to proteolysis (15,38,(42)(43)(44)(45)(46). Following the acidic pH-induced conformational change of HA, L-(tosylamido-2-phenyl ethyl) chloromethyl ketone (TPCK)-treated trypsin digests the HA1 subunit but not the HA2 subunit (42).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit antisera against the H1N1 HA2 C helix were produced via immunization with the A/New Caledonia/20/1999 HA2 C-helix peptide conjugated to keyhole limpet hemocyanin (KLH; Pierce) as described previously (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After viral entry into host cells, M2 conducts protons from acidic host-cell endosomes to the virion interior to allow for uncoating and release of viral RNA. M2 on host-cell endosomal membranes is also observed in some cases to conduct protons to elevate secretory vesicle pH, thereby delaying egress of nascent virion particles and preventing viral hemagglutinin from adopting a nonfunctional, low pH conformation (Sugrue et al, 1990;Alvarado-Facundo et al, 2015). The M2 ion channel of influenza B (B/M2) is a functional homolog of A/M2.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the M2 protein plays a major role in the preservation of the HA native conformation, preventing the premature HA conformational change to the low pH form during the virus transport to the cell surface [64]. Earlier we demonstrated [65] that the M2 protein of the virus A/Singapore/1/1957 CA (H2N2) has lower ion channel activity than the M2 of A/Switzerland/5389/1995 (H1N1).…”
Section: Cell-based Influenza Vaccinesmentioning
confidence: 99%